2007
DOI: 10.1029/2006jd007850
|View full text |Cite
|
Sign up to set email alerts
|

Observed relationship between surface specific humidity, integrated water vapor, and longwave downward radiation at different altitudes

Abstract: [1] Atmospheric water vapor and surface humidity strongly influence the radiation budget at the Earth's surface. Water vapor not only absorbs solar radiation in the atmosphere, but as the most important greenhouse gas it also largely absorbs terrestrial longwave radiation and emits part of it back to the surface. Using surface observations, like longwave downward radiation (LDR), surface specific humidity (q) and GPS derived integrated water vapor (IWV), we investigated the relation between q and IWV and show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

28
133
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 160 publications
(168 citation statements)
references
References 34 publications
28
133
0
2
Order By: Relevance
“…Thus, changes in specific humidity (q) have a greater effect on DLR in cold seasons and at higher elevations where the initial q is smaller. Ruckstuhl et al (2007) present observational evidence from the Alps to support this conclusion. They suggest an enhancement in the absorption of outgoing longwave radiation in the atmospheric window (8-13 lm) at higher elevations where the average atmospheric vapor concentrations are lower.…”
Section: Effect Of Surface Water Vapor On Winter Warmingsupporting
confidence: 76%
See 3 more Smart Citations
“…Thus, changes in specific humidity (q) have a greater effect on DLR in cold seasons and at higher elevations where the initial q is smaller. Ruckstuhl et al (2007) present observational evidence from the Alps to support this conclusion. They suggest an enhancement in the absorption of outgoing longwave radiation in the atmospheric window (8-13 lm) at higher elevations where the average atmospheric vapor concentrations are lower.…”
Section: Effect Of Surface Water Vapor On Winter Warmingsupporting
confidence: 76%
“…The power law relationships described in the figure suggest that significantly large changes occur in DLR owing to changes in q when the latter is less than 2.5 g/kg. The model's power law relationship, obtained using all the data points shown in the figure, is comparable to the power law relationship of Ruckstuhl et al (2007) for all sky conditions in the Swiss Alps. The model's power law does better in capturing the relationship between DLR and q at higher elevations (2,500-5,300 m), whereas the power law from Ruckstuhl et al (2007) does better at 0-2,500 m. The model shows a slightly higher sensitivity of DLR to q as compared to the sensitivity from the power law relationship of Ruckstuhl et al (2007) when q is higher than 0.7 g/kg which is true at all elevations and seasons in the plateau ( Table 2).…”
Section: Effect Of Surface Water Vapor On Winter Warmingsupporting
confidence: 57%
See 2 more Smart Citations
“…6) gives about PWV = 19 mm. Ruckstuhl et al (2007) demonstrated a set of linear relationships between PWV and specific humidity for a range of environments. Using their data from Payerne, Switzerland at about 500 m a.s.l.…”
Section: Multi-hour Interferogram and A Stratified Refractivity Modelmentioning
confidence: 99%